(untitled) (Bangladesh Journal of Neuroscience, 2026)
Background: Cervical dystonia is the most common adult onset focal dystonias and botulinum toxin injection is an effective treatment for this condition. Objective: The objective of the study was to observe immediate (Up to 4 Hours after injection) and Delayed (14 Days after injection) adverse effect of botulinum toxin in cervical dystonia patients. Methology: All cervical dystonia patients attending the Neurology Clinic and aggreed to be injected with botulinum toxin for treatment, Kokilaben Dhirubhai Ambani Hospital and Medical Research Institute, Mumbai, India, from August 2022 to May 2023, were included in the study. 36 patients with cervical dystonia were injected with Botox (Onabotulinum Toxin A, byAllergan). Injections were given by a single expert and dosing was determind by the expert. Results: Out of 36 patients 24 were female (66.66%) and 12 were male (33.33%). Highest number that is 12 out of 36 patients had onset of symptoms between the age of 41 to 60 years of age (33.33%).17 out of 36 patients had torticollis (68%), 9 had retrocolis(25%), 5 had lateroclis(13.88%) and 5 had anteroclis(13.88%).21 (58.34%) out of 36 patients had duration of symptoms more than 5 years.27 patients (75%) out 36 had received treatment with botulinum toxin previously and rest 9 patients (25%) never received botulinum toxin.4 patients(11.11%) had excessive bleeding from injection sites, 3 patients(8.33%)complained of pain but no patient developed anaphylaxis within 4 hours of injection (0). Excessive muscle weakness was observed in 4 patients (11.11%) 14 days after injection followed by dysphasia in 1(2.77%) and persistent hematoma in 1 patient (2.77%) at injection sites. Conclusions: Botulinum toxin is an effective method of treating focal dystonia and in expert hands side effects are minimal.